2009
DOI: 10.1163/156856108x379083
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Moisture in Adhesive Bonds Using Electrochemical Impedance and Dielectric Spectroscopies

Abstract: The ingress of moisture into an adhesive bonded structure can lead to a variety of effects. Moisture has the ability to plasticize the adhesive but may also segregate into microvoids. The water in the voids will have less of an effect as it does not plasticise the matrix and is unable to influence the interface between the resin and the substrate. Only if the T g of the matrix drops below ambient will it allow expansion of the voids and then there will be consequential lowering of the fatigue characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Wahab et al [77] also found that the initial diffusion rate was twice as rapid into laminated adhesive resin discs compared with bulk adhesive. Investigations implementing more advanced methods, such as Fourier transform infrared spectroscopy (FTIR) [78,79], nuclear reaction analysis [81] and electrochemical impedance spectroscopy (EIS) [82,83] also confirm the previous findings. This implies that employing the diffusion coefficient of bulk adhesive specimens would result in an underestimation of the actual moisture content at the interface of steel and adhesive.…”
Section: Interfacial Moisture Diffusionsupporting
confidence: 79%
See 1 more Smart Citation
“…Wahab et al [77] also found that the initial diffusion rate was twice as rapid into laminated adhesive resin discs compared with bulk adhesive. Investigations implementing more advanced methods, such as Fourier transform infrared spectroscopy (FTIR) [78,79], nuclear reaction analysis [81] and electrochemical impedance spectroscopy (EIS) [82,83] also confirm the previous findings. This implies that employing the diffusion coefficient of bulk adhesive specimens would result in an underestimation of the actual moisture content at the interface of steel and adhesive.…”
Section: Interfacial Moisture Diffusionsupporting
confidence: 79%
“…This variation, plus uncertainties resulting from many different combinations of adherents, surface preparations and adhesive materials, has made interfacial diffusion a complicated phenomenon to characterise. However, it is generally accepted that the diffusion process is much faster at the interface compared with bulk adhesive [76][77][78][79][80][81][82][83]. Zanni-Deffarges and Shanahan [76] compared the diffusion rates in bulk adhesive specimens and bonded joints and found that it was greater for adhesive joints.…”
Section: Interfacial Moisture Diffusionmentioning
confidence: 99%